Real Time Motion and Color Detection - Faek, Fatima Kamil; Elyas, Velar Hikmet (Sulaimani Journal for Pure and Applied Sciences, 2015)
When using HD video cameras in stores a large storage space is needed. The required storage space can be decreased using motion and a color detection algorithm that makes the camera records only when a motion or a lighting change occur. So, in this work a real time motion and color detection is presented based on the difference of two successive frames of images after dividing the image into blocks, different block sizes are tested (2×2, 4×4 , and 8×8).YCbCr color system is used for each case with different thresholds for Cb, Cr, and Y. Good results for the motion detection can be obtained using Cb, and Cr other than Y, since the coloring components of an image are exist in Cr, and Cb, which are important for motion detection. Additionally the components that produce or reflect bright light can be obtained from Y. Consequently the result of lightening change detection at different illumination conditions is better using Y more than Cb, and Cr. This means that the best result for both motion, and lighting change detection is obtained by combining the chrominance (Cb, Cr) and luminance (Y) components of a video. The data used in this work are collected in an indoor environment using a laptop webcam under different illumination conditions.
Keywords: Motion detection Color detection Lightening detection Difference of frames